2015
DOI: 10.1158/1078-0432.ccr-14-1873
|View full text |Cite
|
Sign up to set email alerts
|

Sputum microRNA Biomarkers for Identifying Lung Cancer in Indeterminate Solitary Pulmonary Nodules

Abstract: Purpose The early detection of lung cancer in heavy smokers by low-dose CT (LDCT) can reduce the mortality. However, LDCT screening increases the number of indeterminate solitary pulmonary nodules (SPNs) in asymptomatic individuals, leading to overdiagnosis. Making a definitive preoperative diagnosis of malignant SPNs has been a clinical challenge. We have demonstrated that sputum miRNAs could provide potential biomarkers for lung cancer. Here we aimed to develop sputum miRNA biomarkers for diagnosis of malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 26 publications
5
98
0
1
Order By: Relevance
“…Xing et al 43 used a 3-mirna panel (mir-21, mir-31, mir-210) to evaluate sputum, yielding a sensitivity of 80.52% and a specificity of 86.08%. The mounting body of literature highlights the exciting potential of a noninvasive tool of this kind in nsclc diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al 43 used a 3-mirna panel (mir-21, mir-31, mir-210) to evaluate sputum, yielding a sensitivity of 80.52% and a specificity of 86.08%. The mounting body of literature highlights the exciting potential of a noninvasive tool of this kind in nsclc diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of microRNA expression in other body fluids for cancer detection has also been explored. Using Sputum samples, Xing et al showed that a panel of miR-21, miR-31, and miR-210 is able to differentiate malignant and benign solitary pulmonary nodules, with both high sensitivity and specificity (> 80%), in all three cohorts of samples [83]. Hanke et al reported that the ratio of miR-126 to miR-152, and the ratio of miR-182 to miR-152 are indicators of presence of bladder cancer [84].…”
Section: Potential Use Of Microrna As Cancer Biomarkersmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][50][51][52][53][54][55] Reliable quantification of mRNA and microRNA levels for diagnostic and prognostic purposes requires optimal RNA quality and quantity. However, the different instances along the RNA and miRNA analysis workflow can lead to length, sequence, and structure-specific biases in the final expression analysis of a given set of small RNAs.…”
Section: Challenges Faced By the Main Technologies In Nucleic Acmentioning
confidence: 99%
“…Equipment and analysis costs, throughput, and normalization 6,7 still represent obstacles for large-scale nucleic acid biomarker validation [8][9][10][11][12][13][14] and adoption in the clinics [15][16][17] Differences in the nucleic acid purification method, detection technology, and laboratory protocol often lead to different profiling results. Consequently, interpretation of differential expression data and comparisons across different studies has to be done with a note of caution, as standard deviations can span several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%